Analisis Kemampuan Pedagogi Guru SMK yang sedang Mengambil Pendidikan Profesi Guru dengan Metode Deskriptif Kuantatif dan Metode Kualitatif - isnawati isnawati; Niswardi Jalinus; Risfendra Risfendra (Universitas Negeri Padang, 2020)
Abstract— This research aims to analyze the mastery level of pedagogical competence of PPG teachers of SMK, Faculty of Engineering, Universitas Negeri Padang. The research method used was quantitative descriptive and qualitative methods. The data collection techniques were by using a questionnaire, interviews, observation, and documentation. The results of this research showed that the pedagogical competence of PPG teachers of SMK was still low as seen from the average score of each indicator categorized in the less powerful category. The results of this study can be used as an illustration for the future of the learning of PPG teachers of SMK by lecturers in improving the mastery of pedagogical competence. Keywords : Pedagogical Competence, PPG, Teachers of SMK